2003
DOI: 10.2460/ajvr.2003.64.746
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, hematologic findings, and serum and plasma biochemical findings of horses competing in a 48-, 83-, or 159-km endurance ride under similar terrain and weather conditions

Abstract: Among distance groups, distance ridden, speed, level of fitness, and years of experience of horses had little effect on the variables examined. Electrolyte and water supplementation and earlier arrival at the event may be beneficial for horses that are transported long distances to endurance competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 19 publications
(22 reference statements)
10
60
3
Order By: Relevance
“…It has been proposed that the exercise induces change in plasma volume, electrolytes, and acid-base balance that can provoke alterations in urea and creatinine serum levels, depending on several factors, as exercise intensity and duration, training level, thermoregulation, and weather conditions. 44 The lack of significant increase in urea and creatinine levels in our study indicates that exercise intensity and duration were not sufficient to cause changes in corporal fluids.…”
Section: Discussioncontrasting
confidence: 53%
“…It has been proposed that the exercise induces change in plasma volume, electrolytes, and acid-base balance that can provoke alterations in urea and creatinine serum levels, depending on several factors, as exercise intensity and duration, training level, thermoregulation, and weather conditions. 44 The lack of significant increase in urea and creatinine levels in our study indicates that exercise intensity and duration were not sufficient to cause changes in corporal fluids.…”
Section: Discussioncontrasting
confidence: 53%
“…The increase in LDH, CK or AST was observed in exercised race horses (Harris et al, 1998;Kedzierski and Bergero, 2006), after endurance rides (Marlin et al, 2002;Barton et al, 2003) and also after show-jump competitions (Balogh et al, 2001). The total plasma protein also increases after exercise as a result of blood dehydration, but these changes can be lowered by the conditioning process (Hinchcliff et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, most of the parameters in liver, renal and lipid profile showed minor increases in their levels, with a statistically significant difference observed only for ALT, total protein, and albumin. Rarely, a mild increase in plasma glucose concentration and a decrease in triglyceride level were seen in race horses after the races (2,3,5). Similar to this observation, a significant increase in total protein and albumin concentrations has been reported in humans after a marathon running, and is probably a secondary reaction to the effect of dehydration after the races.…”
Section: Discussionmentioning
confidence: 99%
“…The limited increase in the two serum muscle enzymes indicates moderate muscular insult due to road transport. Moreover, several authors have reported a mild to moderate increase in plasma CK activity after severe physical stress or exercise (2,3,20). However, rats and turkeys show a significant increase in CK activity even with mild stress or exercise (19,26).…”
Section: Discussionmentioning
confidence: 99%